Development of Rumah Inklusi support group for children with special needs - Kartono, Drajat Tri; Suryadinata, Theofilus Apolinaris; Zuber, Ahmad; Mundayat, Aris Arif; Akbar, Rezza Dian; Andriani, Lutfi; Bawono, Bachtiar Suryo; Hidayah, Ummul (International Islamic Schools Alliance, 2023)
Handling Children with Special Needs (CSN) requires special knowledge and expertise, so parents and schools with children/students with special needs sometimes experience difficulties in nurturing and implementing inclusive education. The Community Service Team from Universitas Sebelas Maret and the Yayasan Lembaga Pendidikan Al Firdaus developed the Rumah Inklusi and ARCHANA to provide CSNs and their families. This study examines the development of support groups for inclusive homes and the implementation of assisting parents with special needs through support groups. The approach used is Participatory Action Research (PAR), which assists parents with special needs at the Al Firdaus Inclusion School with psychologists, pedagogues, and sociologists. Data collection techniques were done through literature studies, Focus Group Discussions, observations, and documentation. The results of the research show that the PAR approach in this service is carried out in four stages: (1) Reflection to determine the problem; (2) Problem-solving design by designing activities for forming support groups and assisting parents with CSN; (3) Implementation through Focus Group Discussion presenting parents and experts in the field of inclusive education; and (4) Evaluation of the implementation of community service activities. Developing inclusion houses is still needed to reach families with special needs, and the benefits can be felt more broadly. This community service activity found the construction gap for children with special needs between schools and families with special needs, which impacts self-acceptance of children's conditions.